Standarisasi Spesifik dan Non Spesifik dari Ekstrak Etanol Daun dandang Gendis (Clinacanthus nutans) - Wijaya, Sumi; Setiawan, Henry Kurnia; Purnama, Veronica Bella (Jurnal Farmasi Sains dan Terapan, 2019)
Standardization of natural materials is needed as an effort to improve the quality and safety of products that are expected to further increase trust in medicines derived from natural ingredients. Snake grass leaf has several pharmacological activities including antioxidants, anticancer, anti-inflammatory, analgesic, enhancing the immune system, antibacterial, antivenom, even there are also uses in the cosmetics field. In this study macroscopic and microscopic observation of Snake grass leaves and determination of specific and non-specific standardization on ethanol extracts of Snake grass leaves have been done. The parameters tested on Snake grass leaf extract include the identity of the extract, organoleptic, ethanol soluble extract, water soluble extract, phytochemical screening, chromatogram profile using TLC, spectrum profile using UV-Vis spectrophotometer, spectrum profile using IR (infrared)spectrophotometer, determination of secondary metabolite content, total ash content, water soluble ash content, acid insoluble ash content, water content, pH, and specific gravity. The results showed the characteristics of ethanol extract of Snake grass leaf in the form of green-black extract, aromatic distinctive odor; ethanol soluble extract content> 54%; water soluble extract content> 37%; phytochemical screening results showed the presence of alkaloid compounds, flavonoids, polyphenols, saponins, steroids and terpenoids; the results of IR spectrophotometer analysis show spectrum profiles in the range wave of numbers 3325-3351 cm-1, 2924-2919 cm-1, 1622 -1633 cm-1, 1341-1345 cm-1 and 1020-1047 cm-1; total phenol levels> 0.16%; total flavonoid levels> 0.11%; total alkaloid levels> 0.03%; water content